Affinity labeling of rat liver thyroid hormone nuclear receptor. - Nikodem, V M (1980)
The thyroid hormone receptor from rat liver nuclei has been covalently labeled with the N-bromoacetyl derivatives of L-thyroxine (T4) and 3,3',5-triiodo-L-thyronine (T3). Displacement binding studies showed that, in the presence of 100-fold molar excess of unlabeled N-bromoacetyl-T3 or T4, binding of [125I]T3 or [125I]T4 was nearly totally inhibited. Heat inactivation of the receptor (55 degrees C for 15 min) resulted in parallel losses in the binding of T3 (95%) and N-bromoacetyl-T3 (93%). These results indicated that T3 and T4 and their bromoacetyl derivatives compete for the same binding site. The nuclear receptor showed identical behavior in high-pressure liquid chromatography (HPLC) whether bound to T3 or T4 or covalently labeled with their bromoacetyl derivatives. HPLC provided a single-step 100-fold purification of the nuclear receptor. Na-DodSO4 gel electrophoresis of the nuclear receptor labeled with N-bromoacetyl derivatives of [125I]T3 or [125I]T4 showed one major radioactive component with a molecular weight of 56,000. Furthermore, in the absence of denaturant, the nuclear receptor either bound to [125I]T3 or covalently labeled with N-bromoacetyl-[125I]T3 showed identical mobility. These results suggested that the nuclear receptor is a single polypeptide chain and binds either T3 or T4. Nuclear receptors covalently linked with N-bromoacetyl derivatives of [125I]T3 or [125I]T4 may be useful as a marker for the preparative purification of receptor.